Use of Net Promoter Score (NPS) in Hospital Marketing Strategy to Increase Patient Satisfaction and Loyalty - Diliasari, Kristanti; Sulistiadi, Wachyu (International Journal of Social Service and Research, 2024)
Net Promoter Score (NPS) in healthcare settings is scrutinized for its effectiveness in enhancing patient loyalty and service quality. This review explores its application in hospitals, aiming to elevate service quality, satisfaction levels, patient experience, and loyalty. Utilizing a comprehensive literature search spanning November 2013-2023, it examines NPS in hospital marketing strategies, highlighting its conceptualization and utilization. While NPS integration in hospitals globally is prevalent, criticisms persist regarding its validity and relevance, particularly concerning biases and predictive capabilities for sales growth. Despite its benefits in improving healthcare services, NPS demonstrates limitations in supporting healthcare enhancement initiatives. Its suitability as a tool for measuring satisfaction, predicting loyalty, and assessing patient experience remains uncertain and contingent upon contextual factors and service nature.